Our Little Friends with Big Roles: Alterations of the Gut Microbiota in Thyroid Disorders - Ejtahed, Hanieh-Sadat; Angoorani, Pooneh; Soroush, Ahmad-Reza; Siadat, Seyed-Davar; Shirzad, Nooshin; Hasani-Ranjbar, Shirin; Larijani, Bagher (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2020)
Background: The thyroid gland influences the metabolic processes in our body by producing thyroid hormones, and thyroid disorders can range from a harmless goiter to life-threatening cancer. A growing number of evidence support the link between gut microbiota composition and thyroid homeostasis. Gut dysbiosis can disrupt the normal gut barrier function, leading to immunologic and metabolic disorders. Objective: The aim of this review was to discuss the main features of gut dysbiosis associated with different thyroid disorders. Results: Gut microbiota contributes to thyroid hormone synthesis and hydrolysis of thyroid hormones conjugates. It has been shown that microbial metabolites may play a role in autoimmune thyroid diseases via modulating the immune system. Intestinal microbiota can contribute to the thyroid malignancies via controlling DNA damage and apoptosis and influencing inflammatory reactions by the microbiota- derived metabolites. However, the pathogenic role of altered gut microbiota in different thyroid disorders has not yet fully elucidated. Conclusion: Further research is needed to assess the role of alterations of the gut microbiota in disease onset and development in order to achieve novel strategies for the prevention and treatment of these diseases.
Keywords: autoimmune thyroid diseases